PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN GURAME (Osphronemus gouramy Lac. 1801) YANG DIBERI PAKAN CACING SUTERA (Tubifex sp.) DENGAN DOSIS YANG BERBEDA - zulqifar Jusman; Andi Heryanti Rukka; Nur Hasanah; Eka Rosyida; Irawati Mei Widiastuti; Aswad Eka Putra (Journal of Fish Nutrition, 2022)
Gouramy (Oshpronemus gouramy Lac. 1801) is a native Indonesian fish that has a high market with relatively expensive prices. One of the obstacles commonly faced in the cultivation of gouramy is its slow growth. Silkworm (Tubifex sp.) is a type of natural feed with a high protein to support the accelerated growth of gouramy. The purpose of this study was to determine the absolute weight growth and survival of gouramy with different doses of silkworms. This study used a completely randomized design with 4 treatments and 5 replications. Giving silkworms in Treatment 1 (P1) was 10%, Treatment 2 (P2) 15%, Treatment 3 (P3) 20% and Treatment 4 (P4) 25% of the weight of the biomass. The results of the analysis of variance (ANOVA) showed that silkworm with different doses has significantly different results (P<0.05) on absolute weight growth of gouramy. Then, treatment 4 showed the highest absolute weight growth of 0.0444 g. Meanwhile, the survival of gouramy showed results that were not significantly different (P>0.05).